2017
DOI: 10.1111/cfs.12416
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating self‐determination into substance abuse prevention programming for youth transitioning from foster care to adulthood

Abstract: Youth transitioning from foster care to adulthood are at higher risk for alcohol and substance abuse disorders than general population youth. At the same time, these youths are often recipients of strong clinical intervention, often at levels considered unnecessary, for other mental health or behavioural challenges. Because of this, there is sometimes resistance from providers to offer services such as substance abuse prevention programming as it may be seen as contributing to youths' overclinicalization, stig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Self-Determination Theory (SDT), Shared Decision Making (SDM), and the Lundy Model of Participation have concepts that can be integrated into agency procedures to strengthen client self-determination. The SDT concept of client autonomy lends itself into activities that facilitate the self-determination process as observed in the study by Salazar et al (2018). Whereas adoption of SDM equips clients with tools that explain clinical information and options available to them to aid in reaching informed decisions about their care (Elwyn et al, 2010, p. 971), SDT's concept of client autonomy ensures creation of a supportive environment where client perspectives and interests are considered.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Self-Determination Theory (SDT), Shared Decision Making (SDM), and the Lundy Model of Participation have concepts that can be integrated into agency procedures to strengthen client self-determination. The SDT concept of client autonomy lends itself into activities that facilitate the self-determination process as observed in the study by Salazar et al (2018). Whereas adoption of SDM equips clients with tools that explain clinical information and options available to them to aid in reaching informed decisions about their care (Elwyn et al, 2010, p. 971), SDT's concept of client autonomy ensures creation of a supportive environment where client perspectives and interests are considered.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Third-party arrangements involved consultations with relatives and other professionals to document the client's wishes and preferences in instances where the identified client had significant limitations in their ability to fully participate in the self-determination process such as older adults with dementia or minors (Clark, 1998;Nordh & Nedlund, 2017;Österholm et al, 2015). Best practices reported in the articles were informed by models such as Self-Determination Theory's (SDT) concept of client autonomy (Dennis, McCallion, & Ferretti, 2012;Lukens et al, 2013;Salazar, Noell, Cole, Haggerty & Roe, 2018), Shared Decision Making (SDM) reported by Lukens et al (2013), and the Lundy Model (Kennan et al, 2019). Use of SDT principles allowed practitioners to operationalize client self-determination beyond what the client wants (Dennis et al, 2012) as practitioners let clients lead, demonstrated respect for clients' decisions, supported clients in making their own decisions, and involved clients in program decision making and evaluation (Salazar et al, 2018).…”
Section: Strategies At the Organizational Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Greeno et al, 2019aGreeno et al, , 2019b indicated 99% of foster youth in their study were indicated for hazardous drinking and 96% of youth drank between 5 and 6 drinks when consuming alcohol, which is considered binge drinking. Caseworkers should deliver substance abuse prevention services nonjudgmentally, empathetically, and in ways that are empowering (Salazar et al, 2018). Training for child welfare workers to address substance abuse with foster youth is strongly recommended (Braciszewski et al, 2018).…”
Section: Preventionmentioning
confidence: 99%
“…For example, Peterson and Reid [10] support interventions that promote empowerment to abstain from substance use, and Brooks et al [11] find that hopefulness is an important component of primary prevention efforts. These approaches are especially common in programs aimed for adolescents, which attempt to deter or delay their engagement in substance use by building social, communication, and coping skills [12][13][14]. Recent literature also explores new delivery methods for prevention strategies.…”
Section: Primary Preventionmentioning
confidence: 99%